Kemampuan Membaca Al-Qur'an di Kalangan Anak Nelayan di Desa Paluh Sibaji Kecamatan Pantai Labu - Aida Syafitri; Mahariah Mahariah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to describe the ability of children to read the Qur'an in Paluh Sibaji Village, Pantai Labu District. The research method used is qualitative with a case study approach. Data collection techniques use observation, interviews, and documentation. Data analysis techniques through the stages: data reduction, data presentation, and drawing conclusions and verification. The results of the study showed that the ability to read the Qur'an among the children of fishermen in Dusun IV, Paluh Sibaji Village, Pantai Labu District is very low. This can be seen from the ability to recognize hijaiyah letters which is still low, students are still confused about distinguishing hijaiyah letters because the location and dots are in the same shape, students also often confuse hijaiyah letters and pronounce hijaiyah letters interchangeably. the ability to pronounce letters is not optimal, this can be seen from the many mistakes that occur in pronouncing letters. Skills in reading the Koran using tajwid are also very minimal. Therefore, it can be seen that there are still many students who do not have a good understanding of the laws of tajwid, such as the law of tajwid ikhfa which gets the title of inadequate.